Bond behavior of BFRP bars with basalt‐fiber reinforced cement‐based composite materials. (22nd August 2020) - Wang, Yan; Li, Zhenxing; Zhang, Chuchu; Wang, Xin; Li, Jiang; Liang, Yaozhe; Chu, Shaohui
Abstract: This study investigated the bond behavior of BFRP bars with basalt‐fiber cement‐based composite materials (BFRCC). The bond behavior was evaluated in terms of the bar type, bar diameter, matrix type, fiber volume, and spiral stirrup presence. The interface failures between the bars and matrix were observed after the experiment. The influence factors of the test groups on the bond‐slip mechanism were analyzed, and an analytical model of the bond‐slip mechanism was established by data fitting. The results show that the interface failures between the bars and the BFRCC matrix were divided into pull‐out failure and splitting failure, the bond‐slip curve had a residual stage and demonstrated periodic decay. Although the bars' diameters had little effect on the bond strength and average slip, the fiber volume strongly influenced it, and the spiral stirrup could effectively prevent splitting failure. A high‐precision bond‐slip model between the BFRP bars and basalt‐fiber cement‐based composite materials (BFRCC) was established.